Analysis of the effect of temperature and raw material mixes on the pyrolysis process with single retort-rocket stove technology on the characteristics of sawdust charcoal briquettes - Syaiful Mansyur; Enda Apriani (International Journal of Industrial Optimization, 2023)
Government-subsidized LPG gas as household fuel for the poor is increasingly scarce. The discourse to return to using traditional fuels emerged because one of the biomass wastes, namely wood processing in the form of sawdust produced by small and medium industries, can be used to replace LPG gas. This study aims to determine the effect of peak temperature and sawdust mixture on making charcoal briquettes with Single Retort-Rocket Stove Pyrolysis Technology. This technology is one of the alternative pyrolysis technology used for self-heating. This technology is cleaner because the smoke can help speed up combustion to be more energy-efficient. The Rocket Stove system allows spreading of heat from the bottom to the top of the reactor. The raw material for use from Mahogany and Sonokeling Sawdust. Both types of sawdust combine with different ratios. Completely Randomized Design (CRD) non-factorial methods showed that all treatments, namely the ratio of sawdust mixtures and the temperature settings used, greatly influenced the proximate value obtained, where all experiments were very significantly different because Fcalculate > Ftable (0.05). The best briquette proximate results were found in an optimum mixture of rosewood and mahogany with a ratio of 70:30 at 350°C with a setting time of 1 hour, which is close to the SNI 01-6235 standard, with respective characteristic values, namely: 5.5% moisture content; ash content 5.3%; bonded carbon 66.2%; volatile matter content of 22.8% and a caloric value of 6470 cal/gr.